Financial Performance of Small-Size Commercial Banks in Kenya: Does Dividend Pay-out Matter? - Morris Karithi Njilu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The study sought to examine the influence of dividend payout on financial performance of small-sized banks in Kenya. The banks have been facing a tremendous decline in financial performance despite their immense role in the country’s economy. With limited empirical literature on their dividend payout policies, and how such policies affect or influence their performance, the study sought to fill the existing empirical and contextual gaps. Through the residual equity theory, the study had an empirical backing that supported the choice of dividend policy and the level of income as key aspects to address dividend payout. Descriptive research design was used in collecting and analysing the data. The target population was the 48 small-sized banks in Kenya usually known as micro-finance institutions. A sample of 192 managers from these institutions was surveyed. A questionnaire was used to collect the data, which was analysed using descriptive and inferential statistics. The findings revealed that the set dividend policies, the annual income and the divided paid annually had a significant role to play in enhancing the financial performance of the small-sized banks in Kenya. It was concluded that the banks were unable to pay dividends in some financial years, thus affecting the ability of the shareholders to continue supporting the institutions. It was recommended that there is need for the management of these institutions to uphold dividend payout just like other financial management practices for them to attract more shareholders and encourage the existing shareholders to offer equity to the institutions for better performance.